Role of standard echocardiography in Anderson–Fabry disease - Conte, Maddalena; Cioffi, Giuseppe; Romeo, Maria Grazia; Petraglia, Laura; Parente, Erika; Poggio, Paolo; Myasoedova, Veronika; Russo, Vincenzo; Lauro, Raffaella; Accardo, Roberta; Leosco, Dario; Parisi, Valentina (Frontiers in Cardiovascular Medicine, 2024)
Cardiac involvement strongly impacts on prognosis in Anderson-Fabry disease (AFD) patients. All cardiac structures, such as the left ventricle and the left atrium, the aorta, the right sections and the heart valves can be affected by morphological and functional abnormalities. Standard echocardiography has a crucial role in the characterization of AFD-cardiomyopathy. Being a diffuse, non-invasive, easily reproducible and inexpensive investigation, echocardiography represents the most appropriate tool for screening AFD-cardiomyopathy. Furthermore, echocardiographic evaluation is the essential imaging method to support the physician also in the follow-up and risk stratification of AFD patients. Therefore, echocardiography is useful in all stages of the disease; both in the pre-clinical stage, to reveal the first signs of cardiac involvement and to guarantee timely treatment; both to estimate the extent of cardiac involvement, define possible complications and evaluate the response to treatment in patients with established cardiomyopathy. The latest advanced echocardiographic techniques, such as speckle tracking analysis, are offering new insights into the early detection of AFD-cardiac involvement, thus suggesting a promising role for echocardiography in selecting appropriate candidates for treatment. In this review we will examine the role of standard echocardiography in AFD, focusing on its use in screening for cardiac involvement, detailed characterization of AFD cardiomyopathy, and risk stratification of AFD patients.